1991
DOI: 10.1007/bf02244209
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of benzodiazepine long-term users: investigation of benzodiazepine consumers among pharmacy customers

Abstract: A sample of 171 benzodiazepine (bzd) users was investigated in the pharmacy where the patients filled in their prescriptions. Of the sample, 29.8% were males and 70.2% were females. About 60% of the patients had their current prescription from a general practitioner, the rest from different specialists. 70.8% stated to take bzds on more than 3 days of the week. The mean duration of intake of the entire sample was 4.5 years. The most frequent reasons for bzd intake were sleep disturbance followed by nervousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…Some users of benzodiazepines would like to stop taking them (8), many due to awareness of their dependence potential (8-10). However, most patients consider their drugs to be useful (10, 11) and in one survey 75% were angry or upset by the suggestion that they should stop (8).…”
Section: Introductionmentioning
confidence: 99%
“…Some users of benzodiazepines would like to stop taking them (8), many due to awareness of their dependence potential (8-10). However, most patients consider their drugs to be useful (10, 11) and in one survey 75% were angry or upset by the suggestion that they should stop (8).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly explained by an increasing population, with an average growth per year of 0.4-0.5% since 1991 and an increasing proportion of older people. 8 Previous research has documented the attitudes of patients and doctors to benzodiazepines, [9][10][11][12][13][14][15] but little has so far been published about their perceptions or experiences of Z drugs, either alone or compared with benzodiazepine hypnotics. Studies of benzodiazepine hypnotics have shown that patients believe that they are more effective and safer than do doctors.…”
mentioning
confidence: 99%
“…Only 11 % of hypnotic users (Mellinger et al 1985) and 15% of anxiolytic users (Mellinger et al 1984) admitted daily use for 1 year or longer. The long term user ofbenzodiazepines is most commonly an older adult with multiple physical health problems and in moderate psychiatric distress (Barnas et al 1991;Mellinger et al 1984;Rodrigo et al 1988). Data from these surveys, prescription databases (Woods et al 1987) and pharmacies ) are remarkably consistent in demonstrating that older adults, not stereotypical 'drug abusers', receive multiple repeat prescriptions for anxiolytics and hypnotics.…”
Section: Epidemiology Of Benzodiazepine Use In Older Adultsmentioning
confidence: 98%